Injection moulding simulation analysis of natural fiber composite window frame - Wan Abdul Rahman, Wan Aizan; Sin, Lee Tin; Rahmat, Abd Razak (Elsevier B.V., 2008)
Study of window frame fabrication by injection moulding process was carried out with the aid of MoldflowÂ® software. Rice husk filled high-density polyethylene was used as the raw material. Solid and hollow designs (A001 and A002) were created to compare the pros and cons of each design. The investigations were carried out on flowing, packing, cooling and costing of injection moulded window frame. At the end of the analysis, the most feasible design was selected to be further undergone stress analysis according to BS EN 14608:2004 and BS EN 14609:2004. Eventually, the mechanical properties were classified according to BS EN 13115:2001. The actual processing conditions of rice husk composite were approximated to softwood at Cross-WLF viscosity model due to unavailability of rice husk plastic composite (RHPC) rheology property. RHPC melt is generally shear thinning, meanings that the viscosity decreases with increasing of shear rates. From the analysis, window frame with hollow design is preferable, since hollow design has advantage of filling, packing, and cooling properties. The hollow design also costs less than solid design of window frame. However, high injection pressure and clamping tonnage are unfavourable for hollow design. A002 hollow design was selected as the most feasible window frame to be fabricated. Stress analysis was done to classify the window frame. The analyses were carried out to determine racking and static torsion resistance. A002 window frame mechanical strength is classified as Class 2 according to BS EN 13115:2001.